2010
DOI: 10.3758/pbr.17.4.536
|View full text |Cite
|
Sign up to set email alerts
|

Value associations of irrelevant stimuli modify rapid visual orienting

Abstract: In familiar environments, goal-directed visual behavior is often performed in the presence of objects with strong, but task-irrelevant, reward or punishment associations that are acquired through prior, unrelated experience. In a two-phase experiment, we asked whether such stimuli could affect speeded visual orienting in a classic visual orienting paradigm. First, participants learned to associate faces with monetary gains, losses, or no outcomes. These faces then served as brief, peripheral, uninformative cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
59
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 21 publications
3
59
3
Order By: Relevance
“…The attentional bias toward CS+ compared with CSÀ was present in the same participants only after-not before-conditioning. Our findings are not consistent with studies showing that neutral stimuli that acquired emotional value through associative learning did not capture attention at early stages of visual processing (Batty, Cave, & Pauli, 2005;Rutherford, O'Brien, & Raymond, 2010). However, these studies used complex stimuli (e.g., abstract stimuli and faces) whereas our experiment used stimuli that were easy to discriminate and that were very different in basic perceptual features: (i.e., each stimulus had a distinct different color: yellow, red and green).…”
Section: Discussioncontrasting
confidence: 99%
“…The attentional bias toward CS+ compared with CSÀ was present in the same participants only after-not before-conditioning. Our findings are not consistent with studies showing that neutral stimuli that acquired emotional value through associative learning did not capture attention at early stages of visual processing (Batty, Cave, & Pauli, 2005;Rutherford, O'Brien, & Raymond, 2010). However, these studies used complex stimuli (e.g., abstract stimuli and faces) whereas our experiment used stimuli that were easy to discriminate and that were very different in basic perceptual features: (i.e., each stimulus had a distinct different color: yellow, red and green).…”
Section: Discussioncontrasting
confidence: 99%
“…Critically, we associated value with a basic stimulus feature-color-rather than more complex conjunctions of features that have failed to capture attention during extinction in previous studies (10)(11)(12)26). The results show that reward-related stimuli do cause significant and persistent distraction as a consequence of reward learning, and thereby reveal an involuntary mechanism of attentional selection that is uniquely value-driven, operating at an earlier level of representation than previously documented.…”
mentioning
confidence: 59%
“…Several recent studies have shown that the voluntary deployment of attention is influenced by reward (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In contrast to the ample evidence that voluntary deployment of attention to taskrelevant stimuli is affected by reward, the evidence for an influence of the value assigned to stimuli through reward learning on involuntary attentional capture is negative or equivocal (10)(11)(12)26). The experiments reported here provide clear evidence that arbitrary reward-related stimuli capture attention involuntarily and persistently as a result of associations that develop rapidly during learning.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations